Establishment of Community-Level Epidemiological Surveillance Systems to Reduce Disease Incidence in Rural Communities of Sierra Leone - Suluku R.; Macavoray A.; Kallon M. N. (Recent Updates in Disease and Health Research Vol. 2, 2024)
Using the native intelligence of rural people to establish a surveillance system reduces morbidity, mortality, poverty, and zoonotic and neglected disease outbreaks among humans and animals. With the high level of animal-human interaction, there was a strong justification for establishing Surveillance sentinels for monitoring zoonotic diseases. People in rural communities constantly interact with domestic and wildlife, placing them at high risk of disease exposure. The study’s main objective was to explore livestock and wildlife disease interface and transmission chains within the human population in the selected communities and establish community-level epidemiological surveillance systems to reduce disease incidence. Health personnel are unevenly distributed, with the majority in the capital cities, making rural communities lack professional health personnel and health care service providers. Poverty limited rural people’s access to healthcare facilities. Emerging disease outbreaks resulting from complicated environmental changes pose a fundamental challenge in low-income countries, impacting the foundation of human and animal health. People find it difficult to reach medical centers due to insufficient funds. The study recorded stories from the people who have been directly affected by the Ebola virus, a zoonotic disease whose spread could have been quickly curbed had surveillance and AHC been fully functional in Sierra Leone. In Sierra Leone, more than half of the population lives in rural communities (58%), with a multidimensional poverty index of 64.8%. The Animal Health Club engaged thirty (30) villages in a focus group discussion and in-depth interview. Animal Health Club used information obtained to develop a semi-structured questionnaire (600) and observed the people during the talks. Community people identify nine sources of diseases, including humans, poultry, wildlife, pets, ruminants’ crops, water, toilets, and garbage dumps. The people elected/selected an executive to organize and nominate people to supervise the nine sources of diseases. Large villages were divided into zones, while smaller villages remained the same. The people identified ten domestic animals and twenty-four wildlife animals in their communities and some diseases associated with them. They also revealed a high level of interaction between domestic, wildlife, and humans in towns and bush in their respective communities. Rural people believed animals transfer diseases to humans in various ways. However, people contract diseases more from human-human interaction than human-animal interaction. The study’s main objective was to explore livestock and wildlife disease interface and transmission chains within the human population in the selected communities and establish community-level epidemiological surveillance systems to reduce disease incidence. Animal Health Club brings people together in a town or village to achieve a common goal and objective. Such unity increases peace and security in the community and improves health, livelihood, food, and human safety in a cheap, long-lasting, and self-sustainable manner.